2019
DOI: 10.1111/ipd.12503
|View full text |Cite
|
Sign up to set email alerts
|

Dental anxiety in schoolchildren with molar incisor hypomineralization—A population‐based cross‐sectional study

Abstract: Background Identifying patients with high levels of DA helps to define the most adequate oral healthcare strategy, especially for pediatric patients. Aim To investigate the association between parental reports of dental anxiety (DA) and molar incisor hypomineralization (MIH) in schoolchildren. Design A cross‐sectional study was conducted in a representative sample of 731 8‐year‐old schoolchildren from the city of Curitiba, Brazil, who were clinically examined (k ≥ 0.75) for the diagnosis of MIH and dental cari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(51 citation statements)
references
References 36 publications
4
44
1
2
Order By: Relevance
“…It is recognized that socioeconomic status is considered an indirect influence on dental fear (5,8). The factors experienced by the child are considered direct influences (5), such as caries (6) and dental pain (5,11), as well as previous history of dental treatment (5,8,24). In this research, significant association between dental fear and monthly family income was found, but some other studies have found no association (4,11).…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…It is recognized that socioeconomic status is considered an indirect influence on dental fear (5,8). The factors experienced by the child are considered direct influences (5), such as caries (6) and dental pain (5,11), as well as previous history of dental treatment (5,8,24). In this research, significant association between dental fear and monthly family income was found, but some other studies have found no association (4,11).…”
Section: Discussionmentioning
confidence: 63%
“…This indicates that CFSS-DS is a reliable instrument for measuring dental fear in children. It is a self-report or parental report questionnaire, and in this research, it was applied directly to children, since it was observed that when using the parental version of the questionnaire, less anxious parents tend to underestimate their children's dental fear, and more anxious parents tend to overestimate it (11). In Brazil, as far as we know, this is the first research that associates dental fear with dental caries and MIH using CFSS-DS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations